A capacity assessment framework for the fit-for-purpose land administration systems: The use of unmanned aerial vehicle (UAV) in Rwanda and Kenya. (March 2021) - Tan, Evrim; Pattyn, Valérie; Casiano Flores, César; Crompvoets, Joep
Highlights: Geospatial technologies are crucial to build complete and up-to-date land administration systems. FFP capacity assessment framework shows the capacity needs for the use of geospatial technologies. The cases in Rwanda and Kenya show dissimilar capacity needs for the use of UAV in land administration. Policymakers can use the framework to develop effective capacity development strategies. Abstract: This article presents a novel capacity assessment framework, coined as Fit-For-Purpose capacity assessment framework (FCAF), to measure the capacity of the land administration system compliant with the Fit-For-Purpose approach. The framework incorporates legal, political, operational, social, technical, and technological capacity conditions and provides a holistic view of the capacity development pathways. The FCAF is designed by merging six capacity dimensions, namely regulations, political system, operational unit, social norms, land recording techniques, and software. FCAF systematically identifies context-specific, enabling and impeding capacity components and thus provides a basis to develop the necessary capacity development strategies and interventions. Specifically, FCAF can serve as a useful heuristic for the development of the capacity development strategies for the adaptation and sustainability of the geospatial technologies in land administration systems. In the article, by assessing the capacity needs for the adaptation of unmanned aerial vehicle (UAV) technology in Rwandese and Kenyan land administration systems, the efficacy of the FCAF is tested. The findings suggest that in Rwanda, capacity conditions are more supportive of an easier uptake of UAV. Nonetheless, weak market conditions and strict regulations concerning UAV call for attention. In Kenya, existing institutional and political challenges in the land administration system raise concerns about the reliability and attainability of UAV under the current framework conditions. Despite that, there are more supportive market conditions in Kenya in comparison to Rwanda and multiple non-governmental and private actors that can bolster the adaptation process into a more sustainable and scalable land administration system.